Recommendations of the Task Force on Biodiversity and Genetically Modified Organisms (GMOS) for the Environment and Forests Eleventh Five Year Plan (2007-2012) - Planning Commission (Planning Commission Government of India, 1966)
The Task Force on Biodiversity and Genetically Modified Organisms (GMOs), chaired by Dr. Suman Sahai, provides strategic recommendations for the Eleventh Five-Year Plan (2007–2012) to strengthen biodiversity conservation and regulate GMOs in India. Key proposals include establishing Biodiversity Management Committees at the panchayat level, creating people's biodiversity registers, and incentivizing farmers for conserving traditional crop varieties. For GMOs, the Task Force advocates legally mandated monitoring committees, public participation in decision-making, liability frameworks for technology providers, and the establishment of a National Bioethics Commission alongside a National Biotechnology Regulatory Authority. Recommendations also address inter-sectoral coordination through a National Board for Strategic Research in Agriculture, the development of sui generis intellectual property rights for livestock keepers, and holistic biotechnology policies supporting sustainable agricultural practices. The report emphasizes community involvement, ethical oversight, and integration of traditional knowledge, aiming to enhance ecological resilience, food security, and agricultural productivity in India.
Government of India Planning Commission New Delhi
Keywords: Biodiversity Conservation; Genetically Modified Organisms; Agrobiodiversity; GM Regulation; Biosafety; Farmers' Rights; Intellectual Property Rights; Sustainable Agriculture; Bioethics Commission; Community Participation; Biotechnology Policy; Ecological Resilience